Pelo Desenvolvimento do Ensino de Geografia Histórico-Crítico: análise dos currículos do ensino fundamental dos municípios de Cascavel (PR) e Bauru (SP) - Gonçalves, Pauliane Pimentel Rhodes (2024)
The critical geography came to prominence in Brazil in the academic sphere from the 1970s onwards and only came to be considered specifically for school teaching in the 1980s, in the midst of the post-corporate-military dictatorship political opening. Wrapped up in many critical strands, the teaching of critical geography took on new directions and dimensions of a neoliberal nature, materializing in educational documents in the subsequent decade, such as the one of greatest national relevance today, the Common National Curriculum Base. In view of this, it is necessary to unveil the field of geography teaching. Thus, the central thesis of this study is that the field of this teaching is not sufficiently systematized in Brazil from a historical-critical perspective. Under the theoretical framework of historical-critical pedagogy, based on Marxist formulations that underlie the historical-dialectic materialist method, the object of study of this research is the teaching of geography and empiricism, the curricula of Cascavel-PR and BauruSP, published documents , respectively, in 2008 and 2016, and which correspond to the first curricular developments based on historical-critical pedagogy. In this way, this investigation sought as a general objective to understand the curricular proposals of Cascavel-PR and BauruSP in order to contribute to the construction of historical-critical geography teaching. As specific objectives, this study presents: 1) To situate, based on bibliographical research, the historical landmarks of the constitution of the field of geography teaching and understand the critical conceptions that are manifested in it; and 2) Analyze the theoretical expressions of historical-critical pedagogy regarding the teaching of geography in the curricular proposals of the municipalities of Cascavel-PR and Bauru-SP; and 3) Indicate the development of historicalcritical geography teaching. It is concluded that the field of geography teaching has not been sufficiently systematized in Brazil from a Marxist perspective and, therefore, does not involve criticality; its direction has been towards the emptying of teaching and its perpetuation, obfuscating possibilities for omnilateral training and the disqualification of school geographic education.